The costs and benefits of duty-free, quota-free market access for poor countries: Who and what matters? - Bouët, Antoine; Laborde Debucquet, David; Dienesch, Elisa; Elliot, Kimberly (International Food Policy Research Institute, 2010)
This paper examines the potential benefits and costs of providing duty-free, quota-free (DFQF) market access to the least developed countries and the effects of extending eligibility for DFQF access to other small and poor countries. Using the MIRAGE computable general equilibrium model, the paper assesses the impact of scenarios involving different levels of coverage for products, recipient countries, and preference-giving countries on participating countries, as well as competing developing countries that are excluded. The main goals of this paper are to highlight the role that rich and emerging countries could play in helping poor countries to improve their trade performance, to assess the distribution of costs and benefits for developing countries, and to determine whether the potential costs for domestic producers are in line with political feasibility in preference-giving countries.